3D CFD Simulation of Reaction Cells, Cooling Cells, and Manifolds of a Flatbed Reactor for CO2 Methanation. Issue 10 (29th July 2020) - Ghaib, Karim
Abstract: The methanation of CO2 has attracted great interest in recent years as a technology to generate renewable synthetic natural gas and to recycle CO2 from different sectors. The actual development state of a flatbed reactor for the methanation of pure stoichiometric feed gas is presented. Additionally, computational fluid dynamics (CFD)‐based design strategies are introduced which can be applied for the development and optimization of different processing units. The results of the reactor development demonstrate a good heat exchange and flow distribution in the reactor. Abstract : The recent progresses in the development of a novel flatbed reactor for the CO2 methanation are presented. The cells and manifolds of the reactor were designed with predetermined goals. The development was carried out by design strategies, in which the key geometric parameters of the reactor parts were systematically varied. The simulations were performed numerically.